THE GUIDELINES FOR INVENTORY AND ASSET MANAGEMENT ON THE GOOD GOVERNANCE OF CHAIBURI NETWORK SURATTHANI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Saikert, Parichart; Somkhaoyai, Teeraphong; Sisuwan , Katsama (Journal of MCU Nakhondhat, 2023)
The objectives of this research are: 1) to study the status of for the inventory and asset management of Chaiburi district for Surat Thani primary education service area office 3 2) to study the guidelines for inventory and asset management on the good governance of Chaiburi district for Surat Thani primary education service area office 3 3) to promote the guidelines for inventory and asset management on the good governance of Chaiburi district for Surat Thani primary education service area office 3. The study was qualitative research. Data were collected via in- depth interviews with 15 people involved, 5 key informants, and focus group discussion by 7 experts for analytic induction. The results of the study revealed that: 1) The status of the status of for the inventory and asset management of Chaiburi district for Surat Thani primary education service area office 3 has a scope of operation in 6 steps, consisting of (1) Planning to determine needs (2) the procurement (3) the disbursement (4) the control (5) the maintenance and (6) the distribution. 2) The guidelines for inventory and asset management on the good governance of Chaiburi network Surat thani primary educational service area office 3 consist of 6 steps which are as follows (1) Planning to determine needs (2) the procurement (3) the disbursement (4) the control (5) the maintenance and (6) the distribution in every operation step together by using the good governance. 3) The experts verified the guidelines for inventory and asset management on the good governance of Chaiburi network Surat Thani primary educational service area office 3 and found that regarding the focus group discussion, the guidelines have suitability, possibility and usefulness which can be applicable.